2011
DOI: 10.1007/s10071-011-0435-0
|View full text |Cite
|
Sign up to set email alerts
|

The use of fruiting synchrony by foraging mangabey monkeys: a ‘simple tool’ to find fruit

Abstract: Previous research has shown that a considerable number of primates can remember the location and fruiting state of individual trees in their home range. This enables them to relocate fruit or predict whether previously encountered fruit has ripened. Recent studies, however, suggest that the ability of primates to cognitively map fruit-bearing trees is limited. In this study, we investigated an alternative and arguably simpler, more efficient strategy, the use of synchrony, a botanical characteristic of a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 43 publications
4
45
0
2
Order By: Relevance
“…Thus, some primates know where the resources are (Garber, 1989;Garber & Paciulli, 1997;Janson, 2007), when to look for them (Janmaat et al, 2006a,b) and what or how much is likely to be available (Cunningham & Janson, 2007a,b). For example, studies on grey-cheeked mangabeys (Lophocebus albigena) suggested that they (i) may use the calls of hornbills to locate fruit (Olupot et al, 1997), (ii) seem to take into account past weather conditions when searching for food, and are more likely to approach trees with fruit at various stages of development than empty trees of the same species (Janmaat et al, 2006b), and (iii) seem to use cues related to synchronous fruiting during foraging (Janmaat et al, 2012). The latter strategy allows prediction of the fruiting state of a large number of trees of the same species without having to check specific trees (Janmaat et al, 2012).…”
Section: (D) Quantitative Statistical Models Based On Direct Observatmentioning
confidence: 99%
“…Thus, some primates know where the resources are (Garber, 1989;Garber & Paciulli, 1997;Janson, 2007), when to look for them (Janmaat et al, 2006a,b) and what or how much is likely to be available (Cunningham & Janson, 2007a,b). For example, studies on grey-cheeked mangabeys (Lophocebus albigena) suggested that they (i) may use the calls of hornbills to locate fruit (Olupot et al, 1997), (ii) seem to take into account past weather conditions when searching for food, and are more likely to approach trees with fruit at various stages of development than empty trees of the same species (Janmaat et al, 2006b), and (iii) seem to use cues related to synchronous fruiting during foraging (Janmaat et al, 2012). The latter strategy allows prediction of the fruiting state of a large number of trees of the same species without having to check specific trees (Janmaat et al, 2012).…”
Section: (D) Quantitative Statistical Models Based On Direct Observatmentioning
confidence: 99%
“…Second, novelty may cause stronger reactions in a familiar environment [Harris & Knowlton, 2001], and the zoo animals live in far smaller enclosures than their wild counterparts. However, the latter are obviously also very familiar with their habitat, [e.g., Janmaat et al, 2012], and continued to show no response toward the novel objects after dozens of passes. Thus, while the comparison cannot be made totally unbiased, the dramatic difference we observed is real and requires explanation.…”
Section: Wild Versus Zoo Orangutansmentioning
confidence: 99%
“…Sooty mangabeys are West African cercopithecid monkeys that live in the rainforests to the west of the Sassandra River (Mittermeier et al, ). They live in groups numbering from 30 to 120 individuals that occupy home ranges estimated at 5 km 2 (Janmaat, ; Shultz & Noë, ). White breasted Guinea fowl are indigenous to West Africa.…”
Section: Methodsmentioning
confidence: 99%